A lexical analysis of Elementary Science 6 - Cera, Teresita G.
Determination of the scientific lexis found in the pupil textbook for Elementary Science 6 produced by the University of the Philippines- Science Educational Center (UP-SEC) was the subject of this study. This book was chosen for analysis based on the provision of the New Educational Development Plan, making the UP-SEC the Research and Development Center for Science and Math for all schools in the country. It sought to find the varied types of scientific vocabulary found in the textbook, the type of scientific vocabulary which obtained the largest percentage of frequency of use and the type of scientific vocabulary the book has.